A Status of Health-related Quality of Life of Renal Recipients at a Transplant Center in Kathmandu - Thapa, Sheela; Basnet, Bidhya; Mahato, Namra; Devkota, Anup; KC, Takma (Journal of Karnali Academy of Health Sciences, 2021)
Background: Renal transplant is considered as the best treatment available to restore renal function in patients with renal failure. Health-related quality of life (HRQOL) is an important indicator for evaluating therapeutic outcomes and mortality in patients with end-stage renal disease. This study aimed to assess health-related quality of life (HRQOL) of renal recipients. Methods: This observational cross-sectional study involved 165 post renal transplant patients from Tribhuvan University Teaching Hospital, which is also the first renal transplant center in Nepal. Health-related quality of life was assessed by face-to-face interviews, using Kidney Transplant Questionnaire (KTQ-25) and scored according to the scoring algorithm of KTQ-25. Results: The mean score of HRQOL was 5.44 ± 0.80, with the highest score for appearance (6.65 ± 0.53) and the lowest for uncertainty/ fear dimension (4.29 ± 1.10). Several factors, including age, occupation, having loan, length of renal replacement therapy and time duration since transplantation were significantly associated with different dimensions of KTQ-25 (all, p < 0.05). Conclusion: As the uncertainty/fear affected quality of life most, counselling programs for recipients are needed focusing on psychological wellbeing. Although funding is available for patients with end stage renal failure from the government, that does not seem to be adequate for them.